The contemporary vision of Urban planning according to the requirements of modernity and spirit of the Times - Ibrahim, Asaim Sabah (Iraqi Journal of Architecture and Planning, 2018)
Seven topics are addressed in terms of formulas in conjunction with the modernity of what planning is according to the level of being vague and it is: Math logic and its’ relation with planning, Philosophy and its’ relation with planning, policies and its’ relation with planning, Freedom and its’ relation with planning, Demography and its’ relation with planning Society and it’s its’ relation with planning, art and its’ relation with planning. Putting ahead and behind and extracts all the thoughts that related to the after modernity in implication and this research is about to raise a planning that is aligned with spirit of the era and societies’ march connected with a form that is aware to the reality as mess blended with fog to formulate some science and arts that is not free of planning touches.